2016
DOI: 10.1016/j.arr.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E (APOE) ε4 and episodic memory decline in Alzheimer’s disease: A review

Abstract: Autobiographical memory, or memory for personal experiences, allows individuals to define themselves and construct a meaningful life story. Decline of this ability, as observed in Alzheimer’s Disease (AD), results in an impaired sense of self and identity. We present a critical review of theories and findings regarding cognitive and neuroanatomical underpinnings of autobiographical memory and its decline in AD and highlight studies on its clinical rehabilitation. We propose that autobiographical recall in AD i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 158 publications
(95 reference statements)
4
38
1
Order By: Relevance
“…Consistent with prior findings [43], the ε4 carriers in our sample had significantly greater decline in episodic memory than non-carriers, which was independent of the longitudinal memory differences that we found between the SCD groups. This result is consistent with prior work suggesting that APOE ε4 positivity and SCD may have an additive effect on episodic memory decline [34].…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with prior findings [43], the ε4 carriers in our sample had significantly greater decline in episodic memory than non-carriers, which was independent of the longitudinal memory differences that we found between the SCD groups. This result is consistent with prior work suggesting that APOE ε4 positivity and SCD may have an additive effect on episodic memory decline [34].…”
Section: Discussionsupporting
confidence: 92%
“…We also found that cognitively intact APOE-ε4 carriers had significantly poorer performance on RAVLT indices than non-carriers, consistent with research showing poorer episodic memory performance during this clinically asymptomatic stage (El Haj et al, 2016; Twamley, Ropacki, & Bondi, 2006). …”
Section: Discussionsupporting
confidence: 88%
“…The results of the impact of the APOE ‐ε4 carrier genotype on EM deficits have been inconsistent . In this study, we found a possible effect of APOE ‐ PICALM interactions on EM deficits, which have not been previously reported in patients with AD.…”
Section: Discussioncontrasting
confidence: 81%